2015
DOI: 10.1142/s1793042115500438
|View full text |Cite
|
Sign up to set email alerts
|

On the periodic writing of cubic irrationals and a generalization of Rédei functions

Abstract: In this paper, we provide a periodic representation (by means of periodic rational or integer sequences) for any cubic irrationality. In particular, for a root α of a cubic polynomal with rational coefficients, we study the Cerruti polynomials µUsing these polynomials, we show how any cubic irrational can be written periodically as a ternary continued fraction. A periodic multidimensioanl continued fraction (with pre-period of length 2 and period of length 3) is proved convergent to a given cubic irrationality… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 31 publications
0
8
0
1
Order By: Relevance
“…This concludes the proof of Lemma 8. 19. (Note that all the estimations of this proof checked directly by symbolic computations in MAPLE2020, see Case-2.mw in [11]).…”
Section: Thenmentioning
confidence: 99%
“…This concludes the proof of Lemma 8. 19. (Note that all the estimations of this proof checked directly by symbolic computations in MAPLE2020, see Case-2.mw in [11]).…”
Section: Thenmentioning
confidence: 99%
“…Finally, let α be the real root largest in modulus of t 3 −pt 2 −qt−r, with p, q, r ∈ Q. In [12], the author showed that matrix…”
Section: Approximations Of Cubic Irrationalitiesmentioning
confidence: 99%
“…yields simultaneous rational approximations of α − p and r α . However, in [12] the author did not focus on the study of rational approximations, but studied matrix C in order to determine periodic representations for any cubic irrational.…”
Section: Approximations Of Cubic Irrationalitiesmentioning
confidence: 99%
“…The periodicity of the Jacobi-Perron algorithm is also related to the study of Pisot numbers [19,20]. Further studies on MCFs can be found in [2,16,29,41]. Continued fractions for p-adic numbers were introduced in three different ways [10,36,37] and subsequently studied by several authors like [7,11,13,21].…”
Section: Introductionmentioning
confidence: 99%